Effects of the combined pollution of cadmium, lead and zinc on the phytoextraction efficiency of ryegrass (Lolium perenne L.). Issue 36 (2nd July 2019) - Zhang, Jun; Yang, Ningning; Geng, Yani; Zhou, Jinhong; Lei, Ji
Abstract : The effects of cadmium, lead and zinc combined pollution on the phytoextraction efficiency of ryegrass ( Lolium Perenne L.) were investigated in this manuscript. Orthogonal experimental design was adopted in pot test. Abstract : The effects of cadmium (Cd), lead (Pb) and zinc (Zn) combined pollution on the phytoextraction efficiency of ryegrass ( Lolium Perenne L.) were investigated in this work. Orthogonal experimental design was adopted in pot test (composition and interaction). The results showed that, with the increase of heavy metal concentration, the accumulation of elements in ryegrass was increased. The order of enrichment in root was Cd > Pb > Zn, was Zn > Pb > Cd in the stem and leaf, and the order of total EF was Cd > Zn > Pb. Ryegrass revealed the strongest enrichment effect on soil Cd and a strong ability to transfer Zn. Besides, ryegrass showed good potential in phytoextraction heavy metal Cd pollution and Cd × Zn combined pollution.